2021
DOI: 10.1002/ajmg.a.62175
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of congenital anomalies among individuals with trisomy 13 in Texas

Abstract: Few population‐based studies have analyzed patterns of co‐occurring birth defects among those with trisomy 13. We evaluated the frequency of all possible combinations of any one, two, three, or four additional co‐occurring birth defects among 736 individuals with trisomy 13 using data from the Texas Birth Defects Registry for deliveries during 1999–2014. We calculated the observed‐to‐expected ratio for each combination, adjusting for the known tendency for birth defects to cluster non‐specifically. To address … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Previous studies have reported a livebirth prevalence for trisomy 13 ranging from 0.41 to 0.55 per 10,000 births (Goel et al, 2019; Loane et al, 2013; Springett et al, 2015). Almost all patients with trisomy 13 syndrome have a variety of severe congenital anomalies, such as congenital heart defects, omphalocele, or holoprosencephaly, leading to high mortality and morbidity (Carey, 2010; Diaz et al, 2021). Trisomy 13 has traditionally been considered a “lethal” condition because of its poor survival prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported a livebirth prevalence for trisomy 13 ranging from 0.41 to 0.55 per 10,000 births (Goel et al, 2019; Loane et al, 2013; Springett et al, 2015). Almost all patients with trisomy 13 syndrome have a variety of severe congenital anomalies, such as congenital heart defects, omphalocele, or holoprosencephaly, leading to high mortality and morbidity (Carey, 2010; Diaz et al, 2021). Trisomy 13 has traditionally been considered a “lethal” condition because of its poor survival prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…Trisomy 13 is characterised by severe developmental delay and multiple congenital anomalies, cardinally orofacial clefts, microphthalmia/anophthalmia and postaxial polydactyly of hands and/or feet 2. In more than 50% of trisomy 13, the following anomalies in specific organs/systems are observed3 4: central nervous system (holoprosencephaly, intellectual disability and deafness), craniofacial appearance (abnormal auricles, microphthalmia/anophthalmia, sloping forehead), skin and limbs (ie, simian crease, hyperconvex narrow fingernails, polydactyly), heart (ventricular septum defect (VSD), patent ductus arteriosis, atrial septal defect (ASD) and dextroposition), renal defects and genitalia (cryptorchidism in males; bicornuate uterus in females).…”
Section: Introductionmentioning
confidence: 99%